Peran Pemerintah Kota Cilegon dalam Pembangunan Sarana Air Bersih Bagi Masyarakat di Daerah Perbukitan Kecamatan Pulomerak - Nanda Sartika; H. E. Rakhmat Jazuli; Ahmad Rayhan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the role of the Cilegon City Government in the development of clean water infrastructure for communities living in the hilly areas of Pulomerak District. Clean water is a fundamental public service that directly affects public health, environmental quality, and social welfare. Using a qualitative descriptive approach, this research analyzes policy frameworks, institutional roles, and implementation practices related to clean water development at the local level. The findings indicate that the Cilegon City Government plays a central role through regulatory authority, infrastructure development, and coordination with local institutions and communities. The development of clean water facilities has contributed to improved access to water, better sanitation practices, and reduced health risks among residents in hilly areas. However, several challenges remain, including geographical constraints, funding limitations, institutional coordination, and environmental sustainability. Community participation and integrated policy implementation emerge as key factors in ensuring the long-term sustainability of clean water services. This study highlights the importance of strengthening local governance capacity and collaborative approaches to achieve equitable and sustainable clean water provision in geographically constrained areas.